PERUBAHAN LIFESTYLE MAHASISWA YANG BEKERJA SEBAGAI SELEBRITI INSTAGRAM (SELEBGRAM) - Regina Aprilia Pakpahan, - (2018)
Skripsiiniadalahhasilpenelitiankualitatifdenganjudul"PerubahanLifestyle mahasiswa yang bekerjasebagaiselebritiinstagram (selebgram)". Tidakdapatdipungkiri pada era globalisasiini, media sosialadalahsesuatuhal yang tidakdapatterlepasdariindividu. Keberadannyamemilikipengaruhbesarterhadapindividu yang menggunakannya, media sosial yang dianggap paling fress pada saatiniadalahinstagram. Instagram digunakan oleh berbagaimacamkalangan dan umur, ada yang memanfatkannyadenganpositifada pula yang memanfaatkannyadengannegatif. Salah satupemanfaatan media sosialinstagramadalahmenjadiselebritiinstagram (selebgram). Pekerjaaninibanyakdilakukan oleh kalanganmahasiswa. Setiapindividupastimengalamibanyakperubahan, salah satunyaadalahperubahanlifestyle. Tujuanutamadariskripsiiniadalahuntukmengetahuifaktor - faktorapasaja yang menjadipendorongdariperubahanlifestylemahasiswa yang bekerjasebagaiselebritiinstagram. Penelitianinimenggunakanpendekarankualitatifdenganmetodestudikasus. Data yang dianalisisadalahhasildariobservasi dan wawancarapenelitidengannarasumber.Subjekdaripenelitianinihanyasatu orang narasumberyaitumahasiswa yang bekerjasebagaiselebritiinstagram. Dari hasilpenelitianadaenamfaktor yang menjadipendorongperubahanlifestyle mahasiswa yang bekerjasebagaiselebritiinstagramyaitusikap, pengalaman, kepribadian, konsepdiri, motif dan presepsi. Enamfaktortersebutberpengaruhterhadapperubahanlifestyle narasumber, tetapiadabeberapafaktor yang paling mendominasiyaitusikap, pengalaman dan motif;---This is a qualitative research with the title is "Students As A Celebrity Instagram Lifestyle". in this era of globalization, social media is something that can not be separated from the individual. Its existence has a major influence on the individuals who use it, social media is considered the most fress at the moment is instagram. Instagram is used by a wide range of backgrounds and age, there are tapped it with others utilize the positive in the negative. Nowadays a lot of students who use instagram as land a job. One of the utilization of social media is becoming a celebrity instagraminstagram (selebgram). This work was done by students. Over time each individual must have undergone many changes, changes prior to using social media instagram or changes after using social media instagram. One is a change in lifestyle. The main objective of this study was to determine the factors - factors that become a driving force of change in lifestyle student working as a celebrity instagram. This study uses pendekaran qualitative case study method. The analyzed data is the result of observation and interview researchers with resource persons. The subject of this research is only one resource that students who worked as a celebrity instagram. From the research there are six factors that are driving change in lifestyle or the lifestyle. Students worked as a celebrity instagraminstagram using social media will change the lifestyle factors driving the change that attitude, experience, personality, self-concept, motives and perception. Six of these factors influence the change of lifestyle resource, but there are several factors that most dominating that attitudes, thoughts and motives.